Truth or reconciliation? A response to Theo de Wit - Roodt, Vasti (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
In my response to Theo de Wit’s paper, I first set out what I consider to be his most important claims about the relationship between evil and narrativity, before asking four questions about some of the implications of these claims: (1) Are we to presume that there is an absolute choice between reconciliation and a full recounting of evil, so that the latter would necessarily preclude the former? (2) Assuming that we are indeed faced with such a choice, what is proper response to it? (3) Is there any hope of a trustworthy account of evil at all, given that deception seems to be endemic in every such account? and (4) What status should we accord to victimhood in general and victims’ narratives in particular?